Ultra-low-dose left ventricular injection-guided computed tomographic angiography prior to transcatheter aortic valve implantation: A novel technique for imaging - Çakal, Beytullah; Çakal, Sinem Deniz; Yıldırım, Aydın (Turkish Society of Cardiology, 2019)
Transcatheter aortic valve implantation (TAVI) has evolved as a novel procedure for the treatment of severe aortic stenosis. Since large-diameter catheters (18-24 F) are required for TAVI procedures, procedural evaluation of the peripheral vascular pathways and precise annular sizing is crucial both for patient selection and guidance of the intervention. However, the population is frequently frail and elderly, and these patients often have a greater prevalence of peripheral artery disease. A 50 to 140 mL intravenous contrast agent is required for computed tomographic angiography (CTA), which may induce contrast-induced nephropathy, particularly when performed in patients with chronic kidney disease.
Transkateter aort kapak değişimi öncesi sol ventrikül enjeksiyonu ile çok düşük doz kontrast kullanılarak bilgisayarlı tomografik anjiyografik görüntüleme: Görüntüleme için yeni bir teknik
Keywords: Transcatheter; Aortic Valve Implantation; Computed Tomographic